Analysis of Waste in the Warehousing Process of PT. Asia Plastik sing Lean Warehousing and Improvement Strategy with Kaizen Method - Putra, M. Rizqy Ifaldhi; Rochmoeljati, Rr. (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
PT Asia Plastik is a plastic packaging manufacturing company that specializes in injection and blow molding. In its warehousing management, PT Asia Plastik often experiences excessive waste with a high lead time of 419 minutes with a value added of 276 minutes. The method used is the application of Lean Warehousing with the Value Stream Mapping (VSM) method for mapping the flow of warehousing and information flow in the company, and making Process Activity Mapping (PAM) as an analysis tool. With Process Activity Mapping (PAM), it can be seen which process (time) is really important and which process (time) can be simplified or eliminated. A total of 50 activities were obtained with details of 16 Value Added activities, 7 Non-Value Added activities, and 27 Necessary Non-Value Added activities. Based on the results of the research, activity simplification and Big Picture Mapping were proposed with a total of 36 new activities compared to 50 old activities, a reduction of 14 activities. Then the time obtained is 370 minutes which was previously 419 minutes, saving 49 minutes. In addition, there are also proposals for improvement with the Kaizen method to reduce existing waste.